CONSUMER ACCEPTANCE OF SEAWEED (Eucheuma cottoni) EXTRACT FROM DRAGON FRUIT SKIN(Hylocereus polyrhlzus) - Nita Kristiani; Dahlia Dahlia; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to determine consumer acceptance of seaweed crackers (Eucheuma cottoni) with the addition of natural dyes from the skin of red dragon fruit (Hylocereus polyrhlzus). The research design was a non-factorial Completely Randomized Design (CRD) with 4 levels of treatment, namely without the addition of red dragon fruit skin extract (W0), 10% red dragon fruit skin extract (W1), 20% red dragon fruit skin extract (W2), and 30% red dragon fruit skin extract (W3). The test parameters on seaweed cracker products were carried out on organoleptic assessment (color, aroma, taste and texture) and proximate analysis (moisture, ash, protein, and crude fiber content). The results showed that the treatment of red dragon fruit skin extract had a significant effect on consumer acceptance characteristics of seaweed crackers through organoleptic assessment (color, aroma, taste, and texture), and proximate value ( moisture, protein, ash, and crude fiber). The treatment with the addition of 10% red dragon fruit skin extract (W1) had a high level of consumer acceptance reaching 94%, with the characteristics of bright pink seaweed crackers, distinctive aroma of dragon fruit, crispy and savory taste of crackers, with a dry and crumbly texture. Seaweed cracker had a moisture content of 9.81%, 3.53% ash, 2.69% protein, and 26.79% crude fiber.Keywords:Consumer acceptance, crackers, Red dragon fruit skin extract